IGAD and Multilateral Security in the Horn of Africa - Farah Hersi, Mohamed. author. aut Link
IX, 233 p. 1 illus.
Keywords: This book delves into the Inter-Governmental Authority for Development's (IGAD) endeavors to enhance security and economic integration in the Horn of Africa. While aspiring to unite and stabilize the region, IGAD faces complex historical, strategic, and geographical challenges. Through a political economy approach, the book showcases IGAD’s strengths and weaknesses and employs neorealist and regional security complex theories to analyze the involvement of states and non-state actors in IGAD's security agenda, particularly in relation to Somalia. The study highlights opportunities and obstacles to sustainable regional integration, offering practical policy suggestions for curbing armed uprisings and inter-state disputes. It dissects the geopolitical dynamics involving international players like the United States and China, as well as regional powers such as Ethiopia, in IGAD's pursuit of security and economic progress. Valuable for researchers, policymakers, and stakeholders invested in the Horn's security and development, the book bridges gaps in the literature, shedding light on African political development, regional peace and security. Mohamed Farah Hersi is Head of Somaliland's oldest research think tank institution, the Academy for Peace and Development, Hargeisa. He received his Bachelor of Laws degree from the University of Hargeisa in Somaliland, his Master of Laws degree from the University of Pretoria in South Africa, and his PhD from the University of Peace in Costa Rica. He has 13 years of experience and expertise in the fields of research, technical consulting service, policy creation and analysis. Adeoye O. Akinola is Head of Research and Teaching at the Institute for Pan-African Thought and Conversation (IPATC), University of Johannesburg, South Africa. He obtained a PhD in Political Science from the University of KwaZulu-Natal, South Africa. He is the co-editor of the IPATC's journal, “Pan-African Conversation: An International Journal”, and specializes in African political economy, resource governance, migration, conflict, and peace studies.